Exploration Of Real Time PCR As A New Diagnostic Method Of Fragile X Syndrome - Elias, Marjanu Hikmah (2010)
Fragile X Syndrome (FXS) is the most common form of inherited mental retardation in males caused by FMR1 gene abnormality associated with CGG repeats expansion and hypermethylation status of its promoter. Methylated alleles usually lead to transcriptional inhibition and consequently loss of Fragile X Mental Retardation Protein (FMRP) production. Chemical modification of cytosine to uracil by sodium bisulfite treatment has provided an additional method for the laboratory diagnosis of FXS, thus avoiding the use of the laborious Southern blot analysis, which is the gold standard test for FXS diagnosis. Thus, a study was done to explore a rapid, easy, reliable and cheap method for FXS diagnosis that can replace the laborious, time consuming and expensive Southern blot method. Genomic DNA was extracted from peripheral blood of 45 clinically diagnosed FXS patients. Samples were treated with sodium bisulfite followed by amplification using real-time multiplex methylation specific PCR (RT-M-MSPCR) with XIST gene as an internal control, followed by melting curve analysis. Our results showed all control samples with known methylation status were correctly diagnosed using Real Time Multiplex Methylation Specific PCR. For method validation purpose, the methylation status of other 45 male patients sample were also successfully diagnosed using our RT-M-MSPCR method and were concordance with the results of the Southern blot.